Motivasi Kerja Karyawan PT Tunggal Jaya Plastik Industry - Ade Novi; Dian Fithriwati Darusmin (Empathy : Jurnal Fakultas Psikologi, 2022)
Employee Motivation Of PT. Tunggal Jaya Plastik IndustryIn the midst of a pandemic situation that is still ongoing today, it certainly has an impact on the health sector, the economic sector, and the industrial sector itself. The aims this study  to determine the dynamic of work employees motivation of PT Tunggal Jaya Plastic Industry. This study uses a qualitative case study method with content analysis techniques and uses triangulation of sources, data, investigators and member checking to validated data. The subjects in this study were three men and one woman who met the criteria, aged 25-60 years,  lives in Bogor, West Java, Indonesia. The method to collect data are non structured interviews and observations non participant. In addition, researchers also conducted documentation to complete the data. The results of this study are found an overview of how the dynamic work motivation of employees of PT Tunggal Jaya Plastic. Tend to experience changes ranging from changes in responsibilities, work effectiveness, appreciation to employees, discipline at work, conflicts between employees, anxiety about pandemic situations, employee commitment, work relations, and employee gratitude.